THE INTAKE OF NICKEL, CADMIUM AND MANGANESE THROUGH THE INGESTION OF GROUNDWATER FROM SEVERAL PRIVATE WELLS FROM BAIA MARE (ROMANIA) METROPOLITAN AREA - ROBA, Carmen Andreea; ROȘU, Cristina; OZUNU, Alexandru; BACIU, Călin (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
There is a strong relationship between drinking water contamination with heavy metals like Pb, Cd, Cu, Mo, Ni, or Cr and chronic diseases such as renal failure, liver cirrhosis, hair loss, and chronic anaemia. The present study evaluates the content of nickel, cadmium and manganese in thirteen private wells from four rural areas located in Baia Mare metropolitan area (NW Romania). Based on the Ni, Cd and Mn concentration, the heavy metals daily intake rates were calculated for the female, male and children who use these water sources as drinking water supplies. The daily ingestion rate of Ni, due to water consumption, was considerably higher for the inhabitants from Tăuţii de Sus (0.38 – 0.96 μg/day/person), while the Cd (0.04 – 0.11 μg/day/person) and Mn (0.53 – 0.98 μg/day/person) ingestion was higher for the inhabitants from Bozânta Mare and Bozânta Mică villages.